RACISM AND STEREOTYPE IN GET OUT MOVIE SCRIPT - Deni Sepna Nurhadi; Hasbi Assidiqi (CALL, 2019)
Racism is a belief or ideology that all members of each racial groups possess characteristics or abilities specific to that race, especially to distinguish it as being either superior or inferior to another racial group. Continuation of a racism is stereotype. Stereotypes are generalized because one assumes that the stereotype is true for each individual person in the category. Literary works applying this concept in many worked and one of them is film. Therefore, the writer is interested in discussing the mentioned topic with objective of the research: To identify how racism constructed in Get Out movie and to analyze the stereotype of racism appeared in Get Out movie. The method used in this research is sociology of literature, because it is appropriate to analyze literary work which focused on the racism attitude in Get Out movie script. The grand theory for the topic is Racism a Short History by George M. Fredrickson and Stereotype as Explanations by Craig McGarty. While the object of this research is Get Out movie script by Jordan Peele. The result of data analysis show that racism constructed by three elements there are dialog, characterization and plot. And stereotype of racism that appeared in Get Out movie is discrimination, prejudice and violence. From the finding of data analysis, it can be concluded that the result of the research is that Get Out movie have a racism content with suitable features that match with the theory. Therefore, it is clear and not surprising if the work indeed has the impression of “racist”, since most of literary work with racism issue does have that kind of impression to the readers or the spectators.Keywords: racism, sociology of literature, movie script